Redesain Pasar Cibarusah Dengan Pendekatan Arsitektur Perilaku - Retno Fitri Astuti; Wawan Hermawan (Prosiding Sains dan Teknologi, 2022)
Cibarusah Market is a traditional market located on Jalan Raya Cibarusah No. 41 Cibarusah Village, City of Cibarusah District, Bekasi Regency, West Java Province. Many new problems have emerged and have caused ineffective community activities in the area such as congestion, vehicle circulation, pedestrian circulation and garbage. Another problem is the ineffectiveness of the market building itself. It is necessary to improve the arrangement of this building so that it becomes more effective and efficient as well as to create a building that attracts people to shop and as the main shopping center in Cibarusah District by using behavioral architectural principles. The methods used to achieve the final design are field survey, data collection, data analysis, concept and final design. Planning includes rearranging kiosks and stalls within the market through grouping by commodity. It is hoped that it will facilitate the control of building utilities. Keywords: Cibarusah Market, Traditional Market, Cibarusah District, Redesign